입원환자 낙상예방 프로그램에서 근력운동의 효과: 낙상 고위험군 노인환자를 중심으로 - 이현옥; Hyun-ok Lee; 이병화; Byung-hwa Lee; 이창희; Chang-hee Lee (보건정보통계학회지, 2017)
Objectives: The purpose of this study is to analyze the changes in the indices of body muscle strength, the indices of muscle strength associated with physical balance, and index of the pain relief between the intervention group who performed the muscle strength exercise and control group who not performed the muscle strength exercise. The study period was from September 7, 2016 to May 12, 2017, and it was conducted after receiving Institutional Review Board approval. Methods: Among 40 participants who were recruited in this study, the final analysis subjects were a total of 39 people, excluding the one people who dropped out during the 2-week. For analysis, the changes were compared with baseline and after two weeks by comparing three types of body muscle strength indices, four types of physical balance indices, and one type of pain relief index. Finally, we analyzed whether there is a difference between the groups in the each changes. Results: In the body muscle strength index change analysis, the change of muscle mass relative to weight was not statistically significant, but the difference between the groups regard to change was statistically significant (p<0.05). The lower body strength and the bone mineral were statistically significant in both the intervention and control group, but the difference between the groups regard to change was not statistically significant. In the index of muscle strength associated with physical balance change analysis, the intervention group showed improvement much higher in the right arm, left arm, right leg, and left leg of muscle mass than the control group. Also, the muscle mass of the right arm and the left arm was statistically significant in the analysis of the difference between the groups regard to change (p<0.05). Analysis of changes in pain relief index showed that the intervention group showed significantly improvement higher than the control group, and the difference between the groups regard to change was statistically significant (p<0.05). Conclusions: In the elderly patients in the hospital where the fall prevention program was provided, it was concluded that the intervention group higher improved the muscle strength associated with physical balance and the pain relief compared with the control group.